2018
DOI: 10.1101/464628
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibiotic killing of diversely generated populations of non-replicating bacteria

Abstract: Non-replicating bacteria are known to be (or at least commonly thought to be) refractory to antibiotics to which they are genetically susceptible. Here, we explore the sensitivity to killing by bactericidal antibiotics of three classes of non-replicating populations of planktonic bacteria; (1) stationary phase, when the concentration of resources and/or nutrients are too low to allow for population growth; (2) persisters, minority subpopulations of susceptible bacteria surviving exposure to bactericidal antibi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…In parallel, we tested colistin and mitomycin C as molecules reported to demonstrate bactericidal efficacy against metabolically repressed cells (McCall et al, 2019;Grassi et al, 2017;Kwan et al, 2015). Consistent with previous literature (Lopatkin et al, 2019;Lobritz et al, 2015;Gutierrez et al, 2017;McCall et al, 2019;Grassi et al, 2017;Kwan et al, 2015), ampicillin and ciprofloxacin lost significant bactericidal efficacy against nutrientdepleted cells, whereas colistin and mitomycin C retained this activity. Gentamicin exhibited concentration-dependent bactericidal efficacy against resource-depleted cells; specifically, at concentrations >153 the minimum inhibitory concentration (MIC) (Figure S1A), we observed significant bacterial cell killing under nutrient-depleted conditions (Figure 1C).…”
Section: Quantification Of Metabolism Dependence Across Antibiotic Classessupporting
confidence: 71%
See 3 more Smart Citations
“…In parallel, we tested colistin and mitomycin C as molecules reported to demonstrate bactericidal efficacy against metabolically repressed cells (McCall et al, 2019;Grassi et al, 2017;Kwan et al, 2015). Consistent with previous literature (Lopatkin et al, 2019;Lobritz et al, 2015;Gutierrez et al, 2017;McCall et al, 2019;Grassi et al, 2017;Kwan et al, 2015), ampicillin and ciprofloxacin lost significant bactericidal efficacy against nutrientdepleted cells, whereas colistin and mitomycin C retained this activity. Gentamicin exhibited concentration-dependent bactericidal efficacy against resource-depleted cells; specifically, at concentrations >153 the minimum inhibitory concentration (MIC) (Figure S1A), we observed significant bacterial cell killing under nutrient-depleted conditions (Figure 1C).…”
Section: Quantification Of Metabolism Dependence Across Antibiotic Classessupporting
confidence: 71%
“…We note here that while nutrient availability is an effective means through which bacterial metabolic state can be modulated, previous work has shown that treatment of cells with bacteriostatic antibiotics also suppresses metabolic activity (Lobritz et al, 2015;Lin et al, 2014), which inhibits further killing by bactericidal antibiotics from the b-lactam, quinolone, and aminoglycoside classes (Lobritz et al, 2015;McCall et al, 2019). Indeed, we confirmed that a 30-min pre-treatment with the bacteriostatic agent chloramphenicol protected E. coli from killing by ampicillin, ciprofloxacin, and gentamicin, but not from colistin and mitomycin C (Figures S2G-S2K), consistent with our observations of bacterial cell killing by these antibiotics in media of varying richness.…”
Section: Quantification Of Metabolism Dependence Across Antibiotic Classesmentioning
confidence: 85%
See 2 more Smart Citations
“…This investigation aimed to face the analysis of DAP-R mechanisms in MRSA strains on the basis of the acquired knowledge and considering new aspects. First, the "already known" DAP-R mechanisms (dlt over-expression, mprF mutations, and increased net positive cell-surface charge) do not always correlate with changes in DAP minimum inhibitory concentrations (MICs) (Mishra et al, 2014); second, during an infection, the bacteria elapse long periods in limited/arrested growth as in the late growth phases (Kolter et al, 1993); third, DAP is also active on non-dividing and not metabolically active bacteria (Mascio et al, 2007;McCall et al, 2019).…”
Section: Introductionmentioning
confidence: 99%